Our Constitution : an introduction to India's Constitution and constitutional law - Kashyap, Subhash C.; National Book Trust; India (New Delhi : National Book Trust, India, 2001)
A commentary and study.
Keywords: Constitutional law -- India; Constitutional history -- India